Evaluation and correction of localization errors in Wireless Sensor Networks - Adelere, Moses (My University, 2018)
Wireless Sensor Networks have got a lot of attention in the recent years. Wireless sensors can exist as small as a coin, and are inexpensive in term of cost, with low energy consumption and limited computing power. Applications using wireless sensors have also increased, with examples in defence, healthcare, disaster management, and industrial applications. For these reasons, there is a need to accurately detect and allocate faults in our application when they arise. The aim of this Master's thesis is the evaluation and correction of localization error in wireless sensor networks by using NS-2 as a testbed. A Kalman Filter has been used to improve the localization. Security is one examples of such application, where any inaccurate information can lead to loss of valuable assets, or even worse loss of lives. NS-2 provides a platform to examine localization techniques with aid of signal attributes such as Received Signal Strength (RSS), Time of Arrival (ToA), Triangulation etc. Several localization algorithms and scenarios have been considered.
Keywords: WSN; RSSI; ToA; NS-2; Kalman Filter; fi=Tietoliikennetekniikka|en=Telecommunications Engineering|; fi=Master's Degree Programme in Telecommunication Engineering|en=Master's Degree Programme in Telecommunication Engineering|